2021
DOI: 10.1186/s43054-021-00079-7
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 gene and IL2RA rs11594656, rs2104286 gene variants: additional insights of polygenic single-nucleotide polymorphisms’ pattern among Egyptian children with type 1 diabetes

Abstract: Background Type 1 diabetes mellitus (T1D) results from environmental and genetic factors. We aimed to investigate the distribution of PTPN22, IL2RA rs11594656, and rs2104286 variants and its association with T1D in children. A case-control study conducted on 100 diabetic patients and 100 control children. PTPN22 gene, IL2RA rs11594656, and rs2104286 polymorphisms study were done by PCR followed by restriction fragment length polymorphism (RFLP) assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[11][12][13][14][15][16][17] Yet, the CT genotype is not exclusive for AIT, it was reported in children with diabetes mellitus type 1 (T1DM), where it is more dominant followed by CC and TT, in vitiligo and immune skin diseases. [18][19][20] Central hypothyroidism was observed in 83.9% of participants. According to Pierce et al (2017), thyroid dysfunction in DS was more common than in non-DS children, but the disorder was mostly transient.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Yet, the CT genotype is not exclusive for AIT, it was reported in children with diabetes mellitus type 1 (T1DM), where it is more dominant followed by CC and TT, in vitiligo and immune skin diseases. [18][19][20] Central hypothyroidism was observed in 83.9% of participants. According to Pierce et al (2017), thyroid dysfunction in DS was more common than in non-DS children, but the disorder was mostly transient.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study showed that the TT-1858 genotype was more prevalent in children with T1DM ( p = .038, OR: 3.16; 95% confidence interval (CI): 1.28–7.09). The study concludes that PTPN22 C1858T polymorphisms increased the risk factor of T1DM [ 27 ]. Other studies also suggest that the prevalence of the PTPN22 variant (rs2542151), the G allele, may increase the risk of T1DM [ 28 ].…”
Section: Discussionmentioning
confidence: 99%